Atypical Manifestation of X-linked Agammaglobulinemia - the Importance of Genetic Testing - Markocsy, Adam; Kapustová, Daniela; Čereš, Andrej; Froňkova, Eva; Jeseňák, Miloš (Acta medica (Hradec Kralove), 2024)
X-linked agammaglobulinemia (XLA) was one of the first inborn errors of immunity to be described. It is caused by pathogenic variants in the gene for Bruton tyrosine kinase (BTK), which has important functions in B cell development and maturation. Recurrent bacterial infections in the first two years of life and hypogammaglobulinemia with absent B cells in male patients are the most common symptoms. A four-month-old male patient underwent surgical removal of urachus persistens complicated with recurrent scar abscesses. Hypogammaglobulinemia (IgG, IgA, and IgM), low phagocytic activity, mild neutropenia, and a normal percentage of B cells were observed in the patient's immune laboratory profile. Over time, he suffered recurrent respiratory infections (otitis media and rhinosinusitis) and developed B cell depletion, but interestingly, this was with a normalisation of IgG and IgA levels along with undetectable IgM. Molecular-genetic testing confirmed the presence of the pathogenic variant c.1843C>T in the BTK gene, which is associated with a milder phenotype of XLA. Molecular-genetic testing uncovers the variability of clinical and laboratory features of apparently well-known inherited disorders. Patients with mild "leaky" XLA may have normal levels of non-functional or oligoclonal immunoglobulins.
Keywords: Genetic Testing; Male; Genetic Diseases, X-Linked; Agammaglobulinaemia Tyrosine Kinase; genetické testování; Infant; Agammaglobulinemia; X-linked agammaglobulinemia; mužské pohlaví; molecular-genetic testing; proteinkinasa BTK; lidé; atypical leaky phenotype; Humans; kojenec; Inborn error of immunity; genetické nemoci vázané na chromozom X; BTK gene; agamaglobulinemie